Hybrid Improper Ferroelectricity in Highly Cleavable Single Crystals of Dion‐Jacobson‐Compound CsBiNb2O7. (29th December 2021) - Fang, Xiaochen; Hu, Rongwei; Wang, Yazhong; Huang, Fei‐Ting; Cheong, Sang‐Wook
Abstract: Dion‐Jacobson compound CsBiNb2 O7 exhibits supposedly hybrid improper ferroelectricity (HIF), resulting from two different structural distortions. The highly‐cleavable single crystal of CsBiNb2 O7 has been successfully grown and found large ferroelectric polarization as large as 30 μC cm ‐2 with the coercivity of 310 kV cm ‐1 from polarization‐electric field measurements on the crystals. Using piezoelectric force microscopy, a systematic study is on the ferroelectric domain structure and dynamics of CsBiNb2 O7, unveiling the rich nature of its domain/domain wall evolution upon poling. The record large switchable polarization in CsBiNb2 O7 among HIF compounds brings HIF closer to the real Pb‐free ferroelectric applications and the high cleavability of CsBiNb2 O7 crystals provides a unique opportunity to explore ultrathin ferroelectrics with in‐plane polarization. Abstract : High quality single crystal of the n  = 2 Dion‐Jacobson compounds CsBiNb2 O7 is successfully grown. P(E) hysteresis loop measurement shows CsBiNb2 O7 single crystals exhibit the highest spontaneous polarization among all the reported hybrid improper ferroelectrics. The structure of ferroelectric domains and domain walls and associated polarization switching behaviors are thoroughly characterized via piezoelectric force microscopy and polarized light microscopy.